Effect of different medicinal plants (Centella asiatica, Hydrocotyle sp. and Orthosiphon stamineus) on development of Spodoptera litura (Fabricus)(Lepidoptera : Noctuidae) - Maznah M.; Zahora Ismail; Ahmad Said S. (Vibus Innovative Publishing Solutions, 2016)
Spodoptera litura a serious pest for many types of plant and the larvae can defoliate many economically important plants especially those have soft leaves texture. Centella asiatica, Hydrocotyle sp. and Orthosiphon stamineus were used widely as medicinal plant for health cure. These three different medicinal plants were supplied to Spodoptera litura larvae to investigate their effects towards S. litura development and leaves weight consumed. Centella asiatica shown highest mean leaves weight consumed with 1518.5 mg followed by Hydrocotyle sp. and O. stamineus with 121.5 mg and 1.69 mg for each. Cumulative leaf weight consumed per larva was highest on C. asiatica with total 478525.20 mg, followed by Hydrocotyle sp. with 3237.22 mg and O. stamineus recorded lowest leaves consumed by the larva with 72.25 mg. Development of S. litura also shown C. asiatica recorded only seven stadia compared to Hydrocotyle sp. and O. stamineus that recorded eight stadia for each medicinal plants.